PENGARUH PROGRAM GERDU KEMPLING DAN PARTISIPASI MASYARAKAT TERHADAP PROGRAM GERDU KEMPLING BIDANG PENDIDIKAN ( Studi Kasus di Kelurahan Tanjung Ma/Kecamatan Semarang Utara/ Kota Semarang) - Kadumbani, Yohanis Lundji; Santoso, Edi; Taufiq, Achmad (Journal of Politic and Government Studies, 2014)
AbstractGerdu Kempling which stands for integrated motion poverty reduction in five key areas of health, economy, education, infrastructure and the environment. Program Implementation Gerdu Kempling be gradual immersion 5 years in 177 villages in the city of Semarang and the program are conducted from 2011-2015 by cooperating with various parties to participate with or near-equal in poverty menanggulang like SKPDs-on education, SOEs, enterprises, Banks, Universities and NGOs. In the first phase of implementation Gerdu Kempling conducted in 32 villages which are the basis of the poverty urban village is one of the districts of Semarang Tanjung Mas Village North. Tanjung Mas is a densely populated area in the city of Semarang, which gave birth to many of the problems of poverty. therefore implementation of Gerdu Kempling directly to the heart of the problem of poverty in the city of Semarang.In this study the authors focus on the implementation of the research problem Gerdu Kempling education in the village of Tanjung Mas with two variables: the size of the impact of policies and levels of community participation. This research uses methods gambungan between qualitative and quantitative neighbor comprehensively to determine the implementation of the program Gerdu Kempling education in the village of Tanjung Mas. Implementation Gerdu Kempling Education Program is divided into two categories: formal and non-formal, formal education programs such as basic education progra a free school, BSM, scholarships from companies and BOS is a program of non-formal education such as skills training.Keywords: Poverty, Policy Gerdu Kempling, Impact of Policies and Public